Trend detection in precipitation data in climatic station - Zeleňáková, Martina; Purcz, Pavol; Hlavatá, Helena (International Conference “Environmental Engineering”, 2017)
Trends and changes in precipitation extremes have been a focus of research over the past decade. Observations show that changes are occurring in the amount, intensity, frequency and type of precipitation. Climate variability has created the need to study subsequent changes in hydroclimatic variables (e.g. rainfall, streamflow and evapotranspiration) to understand the regional effects of climate change. Mainly agricultural activities and water management activities – water supply, urban drainage, and hydraulic structures management are patterned according to rainfall seasonality. Trend detection in precipitation time series is crucial for water resources management. Many researchers all over the word have investigated hydrologic variables trends at various temporal scales. In this paper we investigate the trends in precipitation time series in climatic station Košice, Slovakia in the period 1981–2013. We address the topic of trend detection in precipitation time series combining novel and traditional tools in order to simultaneously tackle the issue of seasonality and interannual variability, which usually characterize natural processes. The analysis proves that, in the case study area, statistically significant trends in precipitation have been undergoing in the last decades, although they have no significant impacts on water resources.